PENGELOLAAN KEUANGAN DAN ASET DESA DALAM RANGKA MEWUJUDKAN KEMANDIRIAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Suwarso Suwarso (Jurnal Idea Hukum, 2017)
Financial management dfan asset village embodies self-sufficiency based on law No. 6 of the year 2014. The method in this research, methods of juridical normative approach, type of juridical normative research, data sources that are used are the primary law and secondary law materials, and analysis in qualitative analysis.            Self-reliance is a process that the Government of the village to perform activities in order to meet the needs with the capabilities of its own. In order to meet the needs of mandiridapat bias village itself does not always depend on the Government, the village must have authority. The authority which granted the village ACT became the basis for the village to action. Financial and asset management of village based on law No. 6 Year 2014 may push embody independence village. Hope fore the laws not only able to push the manifest independence village, but was able to realize self-reliance village. Independence village should be understood that the village was not left alone without the help of the Government/local government or village could be felt themselves do not need government/local government. Whatever the term independence the village or the village existence definitely self-contained villages should remain within the framework of the unitary State of the Republic with its.Keywords: authority, encourage, independence